Inhibitory mechanism of angiotensin-converting enzyme inhibitory peptides from black tea - LU, Yating (J Zhejiang Univ Sci B, 2021)
The aim of this work is to discover the inhibitory mechanism of tea peptides and to analyse the affinities between the peptides and the angiotensin-converting enzyme (ACE) as well as the stability of the complexes using in vitro and in silico methods. Four peptide sequences identified from tea, namely peptides I, II, III, and IV, were used to examine ACE inhibition and kinetics. The half maximal inhibitory concentration (IC(50)) values of the four peptides were (210.03±18.29), (178.91±5.18), (196.31±2.87), and (121.11±3.38) μmol/L, respectively. The results of Lineweaver-Burk plots showed that peptides I, II, and IV inhibited ACE activity in an uncompetitive manner, which requires the presence of substrate. Peptide III inhibited ACE in a non-competitive manner, for which the presence of substrate is not necessary. The docking simulations showed that the four peptides did not bind to the active sites of ACE, indicating that the four peptides are allosteric inhibitors. The binding free energies calculated from molecular dynamic (MD) simulation were -72.47, -42.20, -52.10, and -67.14 kcal/mol (1 kcal=4.186 kJ), respectively. The lower IC(50) value of peptide IV may be attributed to its stability when docking with ACE and changes in the flexibility and unfolding of ACE. These four bioactive peptides with ACE inhibitory ability can be incorporated into novel functional ingredients of black tea.